DEVELOPMENT AND VALIDATION OF SIMULTANEOUS ASSAY OF SUBSTRATES-MARKERS OF MAIN CYTOCHROME P450 ISOFORMS AND THEIR METABOLITES USING HPLC-MS/MS - E. A. Egorenkov; V. V. Smirnov (Разработка и регистрация лекарственных средств)
Simultaneous quantification method of assaying main CYP isoforms substrates-markers and their metabolites in urine using HPLC-MS/MS was developed to determine activity of following isoforms: caffeine/paraxanthine for CYP1A2, losartane/E-3174 for CYP2C9, cortisole/6-β-hydroxycortisole for CYP3A4 and pinoline/6-hydroxy-1,2,3,4-tetrahydro-β-carboline for CYP2D6. Carbamazepine was used as internal standart. Urine was used as biological object, samples were prepared by extraction with ethyl acetate : hexane : diethyl ether (50:35:15) mixture continued with pH correction of urine sample using borate buffer (pH=9,4) and following extraction with ethyl acetate : hexane mixture (50:50). Method was successfully validated and can be put in clinical practice for CYP isoforms activity determination.